Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If the $p^{th}$ term of an arithmetic progression is $\alpha$ and the $q^{th}$ term is $\beta$, prove that the sum of its $p+q$ term is $$\begin{align}\frac{p+q}{2}\frac{(\alpha+\beta)+(\alpha-\beta)}{p-q}\end{align}.$$

Here can we take the $p^{th}$ and $q^{th}$ term as consecutive terms of the arithmetic progression?

share|cite|improve this question
do you mean consecutive? – lab bhattacharjee Dec 18 '12 at 11:12
Yes, It's consecutive. Sorry! – Gamma Dec 18 '12 at 12:44

Let the arithmetic progression be $\langle x_1,x_2,x_3,\dots\rangle$, so that $\alpha=x_p$ and $\beta=x_q$. Let $$S=x_1+x_2+\ldots+x_{p+q}\;,$$ the sum of the first $p+q$ terms. Let $d$ be the constant difference of this progression, so that $x_{k+1}=x_k+d$ for every $k$. Then $x_{q+1}=x_q+d$, $x_{q+2}=x_q+2d$, and in general $x_{q+k}=x_q+kd$. In particular, if we set $k=p-q$, then $x_p=x_{q+k}=x_q+kd$, i.e., $\alpha=\beta+(p-q)d$, and it follows that $$d=\frac{\alpha-\beta}{p-q}\;.$$

Now write out the sum $S$ twice, as shown below, and add:

$$\begin{array}{c} S&=&x_1&+&x_2&+&\ldots&+&x_{p+q-1}&+&x_{p+q}\\ S&=&x_{p+q}&+&x_{p+q-1}&+&\ldots&+&x_2&+&x_1\\ \hline \end{array}$$

On the left you get $2S$. Each column on the right has the form: it contains $x_k$ and $x_{p+q+1-k}$, and its sum is $x_k+x_{p+q+1-k}$. In particular, for $k=p$ we get the sum $x_p+x_{q+1}=\alpha+\beta+d$.

Each column has the same sum (why?), and there are $p+q$ columns, so


If you now put all of the pieces together properly, you’ll get the desired formula.

share|cite|improve this answer

If $a,d$ be the 1st term & the common difference respectively,

$\alpha=a+(p-1)d$ and $\beta=a+(q-1)d$

Solve for $a,d$

The sum will be $\frac{p+q}2\{2a+(p+q-1)d\}$

share|cite|improve this answer
Ok, so i have to consider the $p^{th}$ and $q^{th}$ terms as the consecutive term. Right? – Gamma Dec 21 '12 at 16:57
@Alpha, do you mean $q=p+1$ or $p=q+1?$ – lab bhattacharjee Dec 21 '12 at 17:00
I meant that are $p^{th}$ and $q^{th}$ term are consecutive term of an AP – Gamma Dec 21 '12 at 17:14
@Alpha, no they can be any two term of the A.P. – lab bhattacharjee Dec 21 '12 at 17:22

$$x_p=x_1+(p-1)d=\alpha$$ $$x_q=x_1+(q-1)d=\beta$$



$$d=\frac{\alpha-\beta}{p-q}$$ $$x_1=\alpha-(p-1)d$$ $$S_{p+q}=\frac{p+q}{2}(2x_1+(p+q-1)d)$$



share|cite|improve this answer
up vote 0 down vote accepted

So here I have to consider the $p^{th}$ and $q^{th}$ as the consecutive term so that by doing their difference I can find the Common difference of the whole AP. So,

$a_p=\alpha=a+(p-1)d$   ------- (i)


$a_q=\beta=a+(q-1)d$   -------- (ii)

By substracting (i) and (ii) we get,


After solving them with the sum formula of the AP, $S_n= \frac n2[2a+(n-1)d]$, we can proceed by $\frac{p+q}2\{2a+(p+q-1)d\}$ and can prove that they are equal.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.